LA POLÍTICA ECONÓMICA: ¿POLÍTICA VERSUS ECONOMÍA? Acertijo del2002-2003 - Cárdenas Núñez, Gilberto (2002)
The economic politics of the national governments of the last times in Peru, it has privileged the handling of the power with ends of stability of the President of the Republic that with ends of growth and economic development. It is necessary to revert such a way to conceive the Government and the one manages of the fields of this branch of the economy to achieve improvements in the distribution of the entrance, bigger national production for internal market and export. As well as to channel the investment and technology in integral form.